THE COMPLEX POLYFUNCTIONAL MODIFIERS INFLUENCE ON THE CORROSION OF THE REINFORCEMENT IN THE CONCRETE - Nikiforova, N. A. (Science and Transport Progress, 2008)
In the article the mechanism of metal corrosion and the influence of complex polyfunctional modifiers on corrosion resistance of steel framework in the concrete is examined.